PENGARUH MEDIA VIDEO EDUKASI TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI MASA PANDEMI COVID-19 PADA SISWA KELAS 3-5 SDN 10 LAMBUNG BUKIT - Nurul Shabrina Utami Samosir; Eryati Darwin; Husna Yetti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The World Health Organization (WHO) declared the novel coronavirus outbreak a global pandemic in 2020. Transmission of Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) occurs through direct, indirect, or close contact with sufferers. The delta variant is a variant that spreads quickly and causes severe symptoms. Based on data in England, the delta variant of COVID-19 spreads faster in schools, especially in children aged 7 to 11 years. Health problems related to clean and healthy living habits (PHBS) that have not been appropriately implemented can cause health problems, such as worms, diarrhea, and acute respiratory infections in elementary school children. One of the efforts to prevent COVID-19 and health problems in children is implementing PHBS. Researchers use electronic media in the form of educational videos because it has several advantages compared to other media. This study aims to evaluate the effect of educational video on PHBS during the COVID-19 pandemic in grade 3-5 students at SDN 10 Lambung Bukit. This research is a study that uses a pre-experimental design with one group pretest-posttest. This study was held at SDN 10 Lambung Bukit, Padang City, with a total sample of 60 respondents. This study showed that 19 respondents had less PHBS, 16 had enough PHBS, 16 had good PHBS, and 9 had excellent PHBS. After the educational video was broadcast, a change in PHBS results was obtained in the form of an increase to 17 respondents having excellent PHBS, 17 respondents having good PHBS, 16 respondents having enough PHBS, and ten respondents having less PHBS. This study concludes that educational video media affects PHBS in respondents.